2020
DOI: 10.1007/s00167-020-05854-4
|View full text |Cite
|
Sign up to set email alerts
|

No clinical differences at the 2-year follow-up between single radius and J-curve medial pivot total knee arthroplasty in the treatment of neutral or varus knees

Abstract: PurposeModern total knee arthroplasty (TKA) systems are designed to reproduce the normal knee kinematics and improve patient outcome. The authors compared two different third‐generation medial pivot TKA implants, having a single‐radius or a J‐curve design in their sagittal plane, hypothesizing no clinical differences. MethodsTwo cohorts of 50 patients who underwent primary TKA were first preoperatively matched by sex, deformity, body mass index (BMI), Oxford Knee Score (OKS), Knee society score (KSS) and range… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 34 publications
2
13
0
Order By: Relevance
“…Acknowledging these limitations, the results of this study are consistent with the experimental work of the current and other authors [11,17,[20][21][22][23][24]27,34,38], where contemporary pivoting, fixed-bearing TKA designs have failed to reproduce normal knee kinematics [43]. On the other hand, the TKA pivoting design evaluated in this study and other dual-pivoting designs studied by different authors have demonstrated bettercontrolled kinematics that are correlated to better active flexion [23] and better functional muscle coordination [44,45], favoring clinically detectable improved knee stability.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Acknowledging these limitations, the results of this study are consistent with the experimental work of the current and other authors [11,17,[20][21][22][23][24]27,34,38], where contemporary pivoting, fixed-bearing TKA designs have failed to reproduce normal knee kinematics [43]. On the other hand, the TKA pivoting design evaluated in this study and other dual-pivoting designs studied by different authors have demonstrated bettercontrolled kinematics that are correlated to better active flexion [23] and better functional muscle coordination [44,45], favoring clinically detectable improved knee stability.…”
Section: Discussionsupporting
confidence: 89%
“…Acknowledging these limitations, the results of this study are consistent with the experimental work of the current and other authors [11,17,[20][21][22][23][24]27,34,38], where contemporary pivoting, fixed-bearing TKA designs have failed to reproduce normal knee kinematics [43]. On the other hand, the TKA pivoting design evaluated in this study and other dual-pivoting designs studied by different authors have demonstrated bettercontrolled kinematics that are correlated to better active flexion [23] and better functional muscle coordination [44,45], favoring clinically detectable improved knee stability. From a purely surgical perspective, after a precise surgical balancing of ligaments and soft tissues has been obtained, the medial-conforming design studied in this comparative series, characterized by a 1:1 medial compartment radius ratio and correlated to the asymmetrical tibial baseplate, gives a clear technical advantage in the correct reproduction of the medial dwell point of a natural knee.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…10,11 Despite these advancements in TKA design, which aimed to reproduce a more anatomical kinematic, there is evidence that implant design plays a minor role in the final outcome as opposed to a precise surgical technique. 12 Therefore, proper balancing of soft tissue has become of primary importance as it is estimated that improper balancing causes up to 35% of TKA revisions in the United States. [13][14][15] To address this problem and to make ligament balancing less operator dependent, several advances in technology have been proposed over the past decades.…”
Section: Introductionmentioning
confidence: 99%